Multi - response optimization of injection molding process parameters using moldex 3D - Canh, Le Van (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
The research is an approach to multi - response optimization of injection molding process parameters. In this author uses Moldex 3D to analyse the injection molding process. The experiments are plotted using L9 orthogonal array, which is generated with the help of DOE module in Moldex3D software. The process parameters melt temperature, packing time, Max. packing pressure are optimized by multiple response consideration of max cooling time and warpage. With the help of Moldex 3D software, the desirability function analysis optimal values of process parameters are obtained. The analysis shows optimized process parameters combination of melt temperature, packing time and max- packing pressure which are 250 oC, 6s, and 140 Mpa respectively. The confirm run results show that by this injection molding machine performance can be improved. However, the future work should be needed to analyze multi cavity molding for the part which is more appliable before we can make the real run.